2013
DOI: 10.1637/10383-092412-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a Turkey Herpesvirus Vector Laryngotracheitis Vaccine for Chickens

Abstract: Turkey herpesvirus vector laryngotracheitis vaccine (HVT/LT) expressing the glycoprotein B gene of laryngotracheitis virus (LTV) has been developed. In vitro growth kinetics of HVT/LT were similar to those of parental turkey herpesvirus (HVT), FC-126 strain. Genetic and phenotypic stabilities of HVT/LT after in vitro (in cell culture) or in vivo (in chickens) passage were confirmed by various assays, including Southern blot analysis, western blot analysis, and an indirect immunofluorescence assay. Safety of HV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…A number of HVT vector vaccines have been constructed and evaluated for their characteristics and efficacy against avian pathogens [21][22][23][24][25][26]. There are three important elements in HVT vector vaccines that can impact efficacy of these vaccines in chicken: insertion sites, antigen genes, and promoters.…”
Section: Construction Of Recombinant Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of HVT vector vaccines have been constructed and evaluated for their characteristics and efficacy against avian pathogens [21][22][23][24][25][26]. There are three important elements in HVT vector vaccines that can impact efficacy of these vaccines in chicken: insertion sites, antigen genes, and promoters.…”
Section: Construction Of Recombinant Virusesmentioning
confidence: 99%
“…There are three important elements in HVT vector vaccines that can impact efficacy of these vaccines in chicken: insertion sites, antigen genes, and promoters. Several insertion sites including US2, US10, UL39 [21], and an intergenic region between UL45 and UL46 (UL45/46) [24][25][26] have been evaluated. Out of these potential insertion sites, we demonstrated that insertion of extraneous genes at the UL45/46 site did not alter their capacity to replicate [26].…”
Section: Construction Of Recombinant Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Live attenuated vaccines are effective in reducing mortality, clinical signs [2,3] and controlling the outbreaks of disease [4]. Several recombinant or virally vectored vaccines are also in use or development and include ILTVs with deletions of virulence-related open reading frames (ORFs) [5,6], and fowl-pox virus (FPV) [7] and turkey herpesvirus (HVT) [8,9] expressing specific ILTV glycoprotein genes.…”
Section: Introductionmentioning
confidence: 99%
“…Bivalent recombinant HVT (rHVT) vaccines have been successfully used to induce protection in chickens against several diseases: Newcastle disease (ND) (Reddy et al, 1996;Palya et al, 2012;Rauw et al, 2014), avian influenza (AI) (Rauw et al, 2012;Soejoedono et al, 2012), IBD (Darteil et al, 1995;Tsukamoto et al, 2002;Bublot et al, 2007;Le Gros et al, 2009;Perozo et al, 2009;Lemiere et al, 2011), and infectious laryngotracheitis (Esaki et al, 2013). These rHVT vaccines offer the advantage of inducing an immune response against Marek's disease as well as against a second disease by inserting a foreign gene in the vector that encodes a specific protein to stimulate a protective immune response.…”
Section: Introductionmentioning
confidence: 99%